Study on the relationship between environmental awareness and emphaty in future Chilean teachers - Mendoza Lira, Michelle (2022)
This quantitative research sought to reveal the relationship between the variables of environmental awareness and empathy in teachers in training. For this, the “Environmental Awareness Scale” and the Interpersonal Reactivity Index were applied to a sample of 150 pedagogy students from two Chilean universities. The results revealed that there is no significant relationship between both variables, although -on their own- they show that the teachers in training have intermediate/high levels of empathy and environmental awareness. These findings allow to orient future research on both issues, considering the role of initial teacher training in education on caring for the environment and empathy with it.